A rare case of Raoultella planticola urinary tract infection. A case report with literature review - Kozioł, Magdalena; Lewicki, Marcin; Pawlicki, Mateusz; Łopuszyńska, Anna; Krasa, Aleksandra; Piekarska, Ewa; Krasowska, Danuta (Journal of Education, Health and Sport, 2020)
Urine infections represent 40-50% of all infections in hospitalized patients. The most common uropathogens are E.coli, S.saprophitycus, and less commonly Enterobacteriaceae, such as Proteus mirabilis and Klebsiella pneumoniae. The spectrum of microorganisms isolated in hospital conditions may be wider. Raoultella planticola is a rare cause of human infections, so far only few cases of ZUM with this etiology have been described. A 56-years-old patient, with a history of cardiac disease, with exacerbation of chronic kidney disease, was admitted to the Department of Internal Medicine. The reason for admission was general deterioration. Many abnormalities in laboratory tests were detected. The doctors' attention was focused on the significant bacteriuria. Moreover, the patient reported dysuria symptoms. Material for urine microbiological culture was taken and empirical antibiotic therapy with ciprofloxacin started. The obtained result of urine culture allowed to identify the bacteria by R. planticola. As a result of the applied treatment, the patient's condition improved. An increasing number of infections with R. planticolla etiology is observed. The bacterium may lead to infections in many systems. The group of patients at risk of the disease includes people with renal dysfunction, who are immunosuppressed. Infections of R. planticolla etiology are usually characterized by good antibiotic response and positive prognosis.